The Effect Of The Cooperative Learning Learning Model Using Flash Media And Motivation On Student Achievement In Gas Kinetic Theory Material At High School State 2 Medan Y.S. 2021/2022 - Hutapea, Pinondang (Jurnal Pendidikan Indonesia, 2022)
The aims of this study were: (1) There were differences in physics learning achievements of students who were taught using cooperative learning models using flash animation media compared to cooperative learning without using flash animation media (2). There are differences in learning achievement in groups of students who have high motivation and groups of students who have low motivation (3) Interaction between cooperative learning using flash animation media with motivation in increasing learning achievement. This research is quasi-experimental. The research population was students of class XII Science at High School State 2 Medan Y.S 2021/2022. The sampling technique used a purposive sample consisting of two classes with a total sample of 72 students. The research instruments are learning achievement tests and student learning motivation questionnaires. The test used to obtain data is in the form of multiple choice. The data in the study were analyzed using SPSS 25 with two-way ANOVA. The results of the ANOVA test obtained: 1. The physics learning achievement of students who were taught by the cooperative learning model using flash animation media was higher than the physics learning achievement of students who were taught by the learning model cooperative without using flash animation media. 2. The physics learning achievement of students who have high motivation is higher than the physics learning achievement of students who have low motivation. 3. There is an interaction between cooperative learning models using flash animation media and motivation in improving learning achievement.